THE IMPORTANCE OF ARBITRATION AGREEMENT IN WRITING: INTERNATIONAL, INDONESIA, AND NEW ZEALAND - Thalita, Feren (Transnational Business Law Journal, 2024)
International commercial arbitration has been one of the popular means to solve a dispute, including in Indonesia and New Zealand. In the event the cross-border commercial parties intend to utilize arbitration to solve its present or future dispute, the regarding parties need to provide the basis for international commercial arbitration: arbitration agreement. One of the matters that the parties need to pay attention in regards to the arbitration agreement is formal validity. Formal validity is ruled through Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1958; UNCITRAL Model Law on International Commercial Arbitration; as well as the majority of national arbitration laws. However, different instruments serve different definitions on “arbitration agreement in writing” as the valid form. There is still a conflicting stance on what is internationally agreed as the valid form of arbitration agreement. Consequently, the issue arises from how important it is for the parties to own arbitration agreement in writing based on the perspectives on international arbitration law, Indonesia, as well as New Zealand. This writing utilizes the comparative juridical research between international instruments (Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1958 and UNCITRAL Model Law on International Commercial Arbitration) as well as the national arbitration law of Indonesia and New Zealand. As a result, the writer has concluded that according to international arbitration law as well as the national arbitration law of Indonesia and New Zealand, the arbitration agreement in writing, as a valid form, is important and highly valued.